Nuclear Energy in the Public Sphere: Anti-Nuclear Movements vs. Industrial Lobbies in Spain (19621979) - Sanchez Vazquez, L. (2017)
This article examines the role of the Spanish Atomic Forum as the representative of the nuclear sector in the public arena during the golden years of the nuclear power industry from the 1960s to 1970s. It focuses on the public image concerns of the Spanish nuclear lobby and the subsequent information campaigns launched during the late 1970s to counteract demonstrations by the growing and heterogeneous anti-nuclear movement. The role of advocacy of nuclear energy by the Atomic Forum was similar to that in other countries, but the situation in Spain had some distinguishing features. Anti-nuclear protest in Spain peaked in 1978 paralleling the debates of a new National Energy Plan in Congress, whose first draft had envisaged a massive nuclearization of the country. We show how the approval of the Plan in July 1979, with a significant reduction in the nuclear energy component, was influenced by the anti-nuclear protest movements in Spain. Despite the efforts of the Spanish Atomic Forum to counter its message, the anti-nuclear movement was strengthened by reactions to the Three Mile Island accident in March 1979.